2019
DOI: 10.1590/0074-02760180585
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary study of potentially zoonotic hepatitis E virus genotype 3 from swine in Northeast Brazil

Abstract: Hepatitis E virus (HEV), an emerging virus associated with acute hepatic disease, leads to thousands of deaths worldwide. HEV has already been reported in Brazil; however, there is a lack of epidemiological and molecular information on the genetic variability, taxonomy, and evolution of HEV. It is thus unclear whether hepatitis E is a neglected disease in Brazil or it has low relevance for public health in this country. Here, for the first time, we report the presence of HEV in Northeast Brazil. A total of 119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 28 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…It is important to note that HEV is present in the swine in our country. Several studies are consistent with the presence of HEV, including HEV RNA, in swine herds in Brazil [24][25][26][27] . Studies conducted in Europe with the general population, patients with HIV, solid organ receptors, patients with chronic liver disease and individuals in contact with wild animals / pigs, show a prevalence ranging from 0.6 to 52.5% 7 .…”
Section: Discussionsupporting
confidence: 61%
“…It is important to note that HEV is present in the swine in our country. Several studies are consistent with the presence of HEV, including HEV RNA, in swine herds in Brazil [24][25][26][27] . Studies conducted in Europe with the general population, patients with HIV, solid organ receptors, patients with chronic liver disease and individuals in contact with wild animals / pigs, show a prevalence ranging from 0.6 to 52.5% 7 .…”
Section: Discussionsupporting
confidence: 61%
“…Seroprevalence studies in younger pigs (<10 months) found an anti-HEV IgG prevalence of 8.6% in North region of Brazil [ 57 ] and 69.7% in the Midwest region [ 60 ]. The detection of HEV RNA in stools in this age group was 1.7% in the Northeast region [ 58 ] 7.94% in the North region [ 57 ] and 87.5% in Southwest [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the molecular characterization of HEV strains detected in Brazil, studies showed that all HEVs found in Brazil were classified as HEV-3 (6 studies in humans, 15 in swine and animal products, and 2 on environmental samples). HEV-3 is known to have a zoonotic (swine) origin and the subtypes 3b and 3i were detected in humans [33,40,45] and pigs [61,62,65,66,[68][69][70][71][72], while the subtypes 3c [57,65,71], subtype 3d [61], subtype 3f [57,58,62] and subtypes 3h [61,71] have been only detected in pigs. As molecular studies have been performed using several molecular assays and primer choices, different regions of HEV have been targeted and characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, HEV3 has been the single HEV genotype identified in humans and pigs. This genotype was found in pigs in south, southeast, northeast, and mid-west regions, and also in slaughterhouse's wastewater in the state of Rio de Janeiro (dos Santos et al, 2011Santos et al, , 2009de Oliveira-Filho et al, 2019). The first human case of HEV3 acute infection in Brazil was confirmed in Rio de Janeiro, and associated with zoonotic transmission (Lopes Dos Santos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%